Machine Learning-Based Secure Data Acquisition for Fake Accounts Detection in Future Mobile Communication Networks. (27th January 2022) - Prabhu Kavin, B.; Karki, Sagar; Hemalatha, S.; Singh, Deepmala; Vijayalakshmi, R.; Thangamani, M.; Haleem, Sulaima Lebbe Abdul; Jose, Deepa; Tirth, Vineet; Kshirsagar, Pravin R.; Adigo, Amsalu Gosu
Abstract : Social media websites are becoming more prevalent on the Internet. Sites, such as Twitter, Facebook, and Instagram, spend significantly more of their time on users online. People in social media share thoughts, views, and facts and create new acquaintances. Social media sites supply users with a great deal of useful information. This enormous quantity of social media information invites hackers to abuse data. These hackers establish fraudulent profiles for actual people and distribute useless material. The material on spam might include commercials and harmful URLs that disrupt natural users. This spam content is a massive problem in social networks. Spam identification is a vital procedure on social media networking platforms. In this paper, we have proposed a spam detection artificial intelligence technique for Twitter social networks. In this approach, we employed a vector support machine, a neural artificial network, and a random forest technique to build a model. The results indicate that, compared with RF and ANN algorithms, the suggested support vector machine algorithm has the greatest precision, recall, and F-measure. The findings of this paper would be useful in monitoring and tracking social media shared photos for the identification of inappropriate content and forged images and to safeguard social media from digital threats and attacks.